The Relationship Between the Big Five Personality Factors, Anger-hostility, and Alcohol and Violence in Men and Women: A Nationally Representative Cohort of 15,701 Young Adults - Jones, Roland M. (Journal of interpersonal violence, 2022)
Alcohol consumption is known to have a disinhibiting effect and is associated with a higher likelihood of aggressive behavior, especially among men. People with certain personality traits maybe more likely to behave aggressively when intoxicated, and there may also be variation by gender. We aimed to investigate whether the reason why men and women with certain personality traits are more likely to engage in violence may be because of their alcohol use.The Big Five personality traits and anger-hostility, alcohol consumption, and violence were measured by questionnaire in 15,701 nationally representative participants in the United States. We tested the extent to which alcohol mediates the relationship between personality factors and violence in men and women.We found that agreeableness was inversely associated with violence in both genders. Alcohol mediated approximately 11% of the effect in males, but there was no evidence of an effect in females. Anger-hostility was associated with violence in both sexes, but alcohol mediated the effect only in males. We also found that Extraversion was associated with violence and alcohol use in males and females. Alcohol accounted for 15% of the effect of extraversion on violence in males and 29% in females.The mechanism by which personality traits relate to violence may be different in men and women. Agreeableness and anger-hostility underpin the relationship between alcohol and violence in men, but not in women. Reducing alcohol consumption in men with disagreeable and angry/hostile traits would have a small but significant effect in reducing violence, whereas in women, reducing alcohol consumption among the extraverted, would have a greater effect.